Nurses' and Nursing Students' Perceptions Toward People Living with Obesity: A Scoping Review Protocol - Duval, Karyne; Couturier, Élise; Laferrière, Marie-Claude; Gagnon, Marie-Pierre; Gallani, Maria Cecilia (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2023)
Introduction: There is significant and pervasive weight bias, weight stigma, and weight-based discrimination everywhere today, even in healthcare settings. Studies have shown that health care professionals (HCPs) hold negative perceptions toward people living with obesity (PLO), which results in heightened health risks for patients. Nurses play a central role in health promotion and the health management of PLO. Thus, identifying nurses' and nursing students' perceptions toward PLO within healthcare practice or educational contexts is paramount to consider further exploratory and intervention studies. Objective: We aim to review and map nurses' and nursing students' perceptions toward PLO from available literature. Method: A search of MEDLINE via PubMed, CINAHL Plus with Full Text (EBSCOhost), and PsycINFO (OVID) will be conducted to identify relevant studies in English, French, Spanish, Portuguese, or Italian on nurses' and nursing students' weight bias. The period covered will be from January 1, 2005, onward, including those available up until our scheduled search in January 2024. Two independent reviewers will conduct screening, study selection, and data extraction. Data will be charted according to the study design, the research setting, years and regions of publication, concepts, and use of theoretical models. The results will be summarized and reported, identifying implications for nursing research and practice. Discussion and Research Spin-offs: This scoping review will inform nursing research and facilitate the development of educational and clinical tools aimed at preventing and reducing weight bias among nurses to promote nursing and interdisciplinary care that upholds principles of equity, diversity, and inclusion.